Contributions to Developments of Photoelectron Spectroscopy and X-ray Absorption Fine Structure Applied to Materials Studies - Hung, Nguyen Van (Communications in Physics, 2021)
This work reviews the contributions of author to the developments and applications of Photoelectron Spectroscopy (PES) and X-ray Absorption Fine Structure (XAFS) to materials studies. Focusing on Angle resolved PES (ARPES) the energy distribution is discussed for angle-resolved photoemission from valence bands of single crystals. The important influence of the spectrometer angle of acceptance on the results of X-ray PES (XPS) is investigated in detail. The Plane Density of States (PDOS) is introduced as a new property of the electronic structure. Most meaningful contributions to XAFS consist of the developments of multiple-scattering and anharmonic XAFS theory. Anharmonic correlated Einstein model (ACEM) and anharmonic correlated Debye model (ACDM) have been derived to obtain Debye-Waller factors (DWF) presented in terms of cumulant expansion which describe the thermodynamic properties and anharmonic effects in XAFS of substances contributing to their accurate structural determination. The anharmonic effective potential (AEP) procedure and first shell near neighbor contributions approach have developed to include many-body effects in the one-dimensional model by a simple measure. Based on DWFs a thermodynamic lattice theory has been derived for studying melting curve and eutectic points of binary alloys. Several applications of the derived methods are performed and the good agreement of the calculated results with experiment illustrate the advantages and efficiencies of the achieved developments